![\bf \textit{parabola vertex form with focus point distance} \\\\ \begin{array}{llll} 4p(x- h)=(y- k)^2 \\\\ 4p(y- k)=(x- h)^2 \end{array} \qquad \begin{array}{llll} vertex\ ( h, k)\\\\ p=\textit{distance from vertex to }\\ \qquad \textit{ focus or directrix} \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ (y-3)^2=8(x-4)\implies (y-\stackrel{k}{3})^2=4(\stackrel{p}{2})(x-\stackrel{h}{4})~~ \begin{cases} \stackrel{vertex}{(4,3)}\\ p=2 \end{cases}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2yhcwwdfydub20mrosyi9did05g6szrpug.png)
now, is worthy noticing that the squared variable is the "y", and thus this is a horizontal parabola.
so let's see, the (h,k) pair for the vertex are at (4,3), and we have a positive "p" of 2 units, now, when "p" is positive, it means the parabola is opening to the right-hand-side.
So if we move horizontally from (4,3) over to 2 units to the right, we'll be landing at the focus point of (6, 3).